Market investigations : a new competition tool for Europe? / edited by Massimo Motta, Pompeu Fabra University, Martin Peitz, University of Mannheim, Heike Schweitzer, Humboldt University of Berlin. - Motta, Massimo; Schweitzer, Heike; Peitz, Martin (Cambridge University Press, 2022)
In many economic sectors - the digital industries being first and foremost - the market power of dominant firms has been steadily increasing and is rarely challenged by competitors. Existing competition laws and regulations have been unable to make markets more contestable. The book argues that a new competition tool is needed: market investigations. This tool allows authorities to intervene in markets which do not function as they should, due to market features such as network effects, scale economies, switching costs, and behavioural biases. The book explains the role of market investigations, assesses their use in the few jurisdictions where they exist, and discusses how they should be designed. In so doing, it provides an invaluable and timely instrument to both practitioners and academics.